Prevention of Liver Failure in Extended Hepatic Resection - G. Kh. Mirasova; I. Z. Salimgareev; M. O. Loginov; A. I. Gritsaenko; M. A. Nartaylakov (Креативная хирургия и онкология, 2021)
Background. Postoperative failure is a major cause of adverse outcomes in extensive liver resection. Post-resection liver failure requires intensive, including extracorporeal, care. Issues in correcting liver failure warrant novel approaches to prevent severe cases.Materials and methods. A retrospective analysis of 228 various-extent liver resections included minor (55.7 %), major (26.8 %) and extended (17.5 %) operations for malignant, benign and parasitic liver lesions. The post-resection liver failure rate has ben graded according to ISGLS.Results and discussion. Postoperative hepatic failure developed in 58 (25.4 %) cases, including 5 of 127 minor (3.9 %) resections, 18 major (29.5 %) and 35 of 40 extended resections (87.5 %). Mild class A liver failures were reported in 12.3 %, and severe classes B and C — in 9.2 % and 3.9 % cases, respectively.CT volumetry in place of the number of resected segments is suggested as a criterion to grade the expected post-resection residual liver, with >70 % defining a minor, 36–70 % — major and 25–35 % — extended expected residual liver.A two-staged extended hepatic resection approach is proposed to reduce postoperative liver failure, with vascular radiology-guided right portal vein embolisation (RPVE) or associating liver partition and portal vein ligation (ALPPS) at stage 1.A comparison of extended hepatic resection outcomes (n = 40) showed a significantly higher rate and severity of liver failure in single- vs. two-staged operations (p < 0.05).Conclusion. Liver failure is a leading cause of death in major and extended hepatic resection. Preoperative CT volumetry allows a more accurate volumetric control of expected post-resection residual liver. Two-staged extended hepatic resection can reliably reduce the rate and severity of postoperative liver failure.